Comparative study of acid functionalization of carbon nanotube via ultrasonic and reflux mechanism - Lau, Yien Jun; Mubarak, N. M.; Lau, Sie Yon; Chua, Han Bing; Khalid, Mohammad *; Abdullah, E. C. (Elsevier, 2018)
Multi-walled carbon nanotubes (MWCNTs) have a great potential in wide applications due to their extraordinary physical, thermal and mechanical properties. However, the known shortcomings, such as hydrophobic nature, poor solubility and dispersibility in most solvents have impeded the technology to further develop. In the present study, various types of acid functionalized MWNCTs (f-MWCNTs) samples were prepared. The investigated process parameters include type of acids, acid concentrations, treatment methods, operating temperature and treatment duration. The f-MWCNTs were characterized using Fourier Transform Infrared Spectroscopy (FTIR), Energy dispersive X-ray (EDX), Field Emission Scanning Electron Microscopy (FESEM) and Zetasizer. The optimum conditions for acid functionalization of MWCNTs were achieved by dispersing MWCNTs in concentrated nitric and sulfuric acid mixture (1:3 v/v ratio), via ultrasonication treatment method at 40 °C for 2.5 h. EDX analysis also revealed that, 21.36 wt% of oxygenated functional groups, with no strong detection of inorganic and metal impurities. In addition, FESEM results also revealed that there is no any severe structural damage on the surface. Acid functionalization of MWCNTs via ultrasonic bath methods is more desirable than reflux method as it can result in high yields of MWCNTs with high density of oxygenated functional groups and minimum structural destruction on the surface of MWCNTs.